2021
DOI: 10.3389/fnbeh.2020.575345
|View full text |Cite
|
Sign up to set email alerts
|

miR-96 Inhibits SV2C to Promote Depression-Like Behavior and Memory Disorders in Mice

Abstract: Accumulating evidence continues to emphasize the role of microRNAs as significant contributors to depression-like behavior and memory disorders. The current study aimed to investigate the mechanism by which miR-96 influences depression-like behavior and memory deficit in mice. A depression-like behavior and memory disorder mouse model was initially established by means of intraperitoneal injection with lipopolysaccharide. Memory deficits in the mice were evaluated using the Novel Object Recognition Test and Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…GSH is an important antioxidant, which markedly decreases depression-like behavior in mice intraperitoneally injected with LPS. 57 Furthermore, sesomol supplementation along with intraperitoneal injections of D-galactose also modifies the effects of oxidative stress caused by the Nrf2/ARE antioxidant defense system. 17 In the current work, sesamol alleviated the Nrf2 antioxidant signaling pathway in the brain of DSS-induced colitis mice, which, to the best of our knowledge, has not been found before.…”
Section: Food and Function Papermentioning
confidence: 99%
“…GSH is an important antioxidant, which markedly decreases depression-like behavior in mice intraperitoneally injected with LPS. 57 Furthermore, sesomol supplementation along with intraperitoneal injections of D-galactose also modifies the effects of oxidative stress caused by the Nrf2/ARE antioxidant defense system. 17 In the current work, sesamol alleviated the Nrf2 antioxidant signaling pathway in the brain of DSS-induced colitis mice, which, to the best of our knowledge, has not been found before.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Cell experiments also confirmed that miR-133a and miR-128 targeted Sv2A 3 UTR to inhibit its expression [60]. Another study on the LPS-induced model showed that miR-96 was targeted and negatively regulated SV2C expression in the hippocampal CA1 region, decreased 5-hydroxyindole acetic acid (5-HT) and dopamine (DA) release, and induced the development of depres-sion [61]. MiR-34a-5p expression increased in the hippocampus of mice exposed to chronic stress.…”
Section: Mirnas and Neurotransmission-related Receptorsmentioning
confidence: 81%
“…Intriguingly, the use of an anti-miR to miR-144-3p, administered subcutaneously, has led to a marked reduction in depression-related phenotypes in stress-prone mice [ 152 ]. Similarly, the increased expression of miR-96 has led to a decrease in the synaptic vesicle glycoprotein 2 family protein which is associated with depression-like behavior, while inhibiting miR-96 using anti-miR decreased depression-like behavior and memory impairment in mice [ 153 ].…”
Section: Therapeutic Potentials Of Mirnas In Depressionmentioning
confidence: 99%